Twenty years of diplomatic relations between Vatican City state and Israel = Dwadzieścia lat stosunków dyplomatycznych pomiędzy Państwem Watykańskim a Izraelem - Secler, Bartłomiej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
?Basic Agreement? concluded between the Vatican City State and Israel in 1993 was an important step for the establishment of diplomatic relations. The conclusion of this Agreement is not a question of interreligious and diplomatic, which was associated with the efforts of the Vatican normalization of political relations with various countries.
Keywords: Israel; Vatican City State; relations; Basic Agreement; Izrael; Państwo Watykańskie; relacje; Porozumienie Podstawowe